O lugar e o não lugar da natureza no cotidiano da Educação Infantil - Narrativas docentes em Cartas Pedagógicas - Brito, Beatriz Antunes Fogaça (Universidade Federal de São Carlos, 2024)
The planet is on the brink of environmental collapse. To reverse this condition and postpone the end of the world (Krenak, 2022b), it is urgent to change the way we relate to nature. This research, with a qualitative approach, has as main objective to establish the relationships between childhood and nature based on narratives from early childhood education teachers, constructed from the exchange of Pedagogical Letters (Freitas, 2021). We sought to answer the following question: Are there spaces/possibilities in the practices of early childhood education teachers for true experiences with nature, for the right to freedom and joy? The answer was constructed from an investigation that used different sources to compose the data: 1) analysis of national documents that govern early childhood education; 2) state of knowledge of academic-scientific productions on the topic of early childhood education and nature between the years 2010 and 2022 and 3) appreciation of narratives produced during the year 2023 by teachers working in the first stage of basic education, through letters. It was noted the absence of public policies and training – initial and continuing – on the subject, as well as a still incipient scientific production and the existence of individualized practices of certain institutions and/or teachers. We understand that we are all beings of culture and nature (Ingold, 1995; Tiriba, 2018) and that the unhealthy contours provided by the capitalist regime and the dichotomies originated by modernity have separated us from biophilic, emotional, bodily and affective aspects, causing illness and degradation of the planet, therefore, the importance of investing in professional training and creating policies that ensure the right of babies and children to full-body experiences, culminating in the construction of a Brazilian pedagogy – macunaímica (Sangenis, 2020), exúlica (Souza, 2016; Rufino, 2018), quintaleira (Coutinho et al., 2022) with a verdant curriculum.
The place and non-place of nature on the daily life of Early Childhood Education - Teachers narratives in Pedagogical Letters
Keywords: Educação Infantil; Natureza; Narrativas docentes; Cartas Pedagógicas; Early Childhood Education; Nature; Teachers narratives; Pedagogical Letters; CIENCIAS HUMANAS::EDUCACAO